2022
DOI: 10.7759/cureus.22888
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Profile of Patients Visiting the Post-COVID-19 Clinic at a Tertiary Care Hospital: A Cross-Sectional Study

Abstract: Background: Coronavirus disease 2019 (COVID-19) survivors may continue experiencing diverse symptoms. This study portrays the clinical and laboratory profile of patients with post-acute sequelae of COVID-19’(PASC) at a tertiary care hospital in India. Methodology: This cross-sectional study enrolled patients visiting the post-COVID-19 clinic three weeks after their acute COVID-19 illness. Their clinical, serological, and radiological characteristics were collected and analyzed. Results: O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…In a study conducted in a tertiary hospital, it was reported that gender did not have any effect on post-covid symptoms [13]. In most of the studies conducted in the post-covid period, it was found that the female gender had more symptoms in the postcovid period than the males [14][15][16].…”
Section: Discussionmentioning
confidence: 94%
“…In a study conducted in a tertiary hospital, it was reported that gender did not have any effect on post-covid symptoms [13]. In most of the studies conducted in the post-covid period, it was found that the female gender had more symptoms in the postcovid period than the males [14][15][16].…”
Section: Discussionmentioning
confidence: 94%